Design and Build Thermo Electric Hybrid Power Plant as AGL CBT Laboratory Backup Power Supply - Erlangga, Raihan Prameswahra; Usman, Usman; Chair, Achmad (Universitas Pendidikan Nasional, 2025)
The demand for reliable and environmentally friendly electricity supply has driven the development of more efficient backup power systems. This study aims to design and construct a hybrid power generation installation that combines thermoelectric generators and solar panels as a backup power solution. The system utilizes solar radiation and temperature disparity as primary energy sources, which are then converted into electrical energy and stored in a 200 Ah LiFePO4 battery. The design stages include the selection of key components such as thermoelectric modules, 100 Wp solar panels, maximum power point trackers, battery controllers, and inverters. Simulations and tests were carried out to analyze the system’s performance under the climatic conditions of Medan City. The test results indicate that power can be continuously generated from these two energy sources, providing a stable backup electricity supply. With a modular and efficient structure, this system has the potential to serve as a sustainable energy source that reduces dependence on fossil fuels. This design also holds promise as a prototype for educational purposes and a rapid solution during power outages.